The effect of wet-dry cycles on tensile properties of unidirectional flax fiber reinforced polymers. (15th February 2020) - Mak, Kenneth; Fam, Amir
Abstract: The impact of moisture is a critical research focus for natural fibres. There is a significant decrease in mechanical performance when fully saturated; however, this may not be representative of real-life applications. In this study, the tensile performance of flax fibre reinforced polymers (FFRP) is investigated when exposed to wet-dry cycles. Manufacturing method, fibre type and resin type were varied throughout this research program. Vacuum bag moulded specimens exhibited an increased strength of 19%, increased rupture strain of 105% and reduced tensile modulus of 29% when saturated; however, it reverted to its original state once dried. When exposed to wet-dry cycles, a statistically-significant reduction in mechanical properties began after 3 cycles, with a maximum reduction of 12% strength and 19% stiffness. Conversely, degradation for wet lay-up moulded specimens was delayed until 12 cycles. When epoxy was replaced with an epoxidized pine oil (EPO) blended resin, there was no mechanical difference throughout wet-dry cycles; however, FTIR showed signs of hydrolysis for both resins. Furthermore, the glass transition temperature of epoxy reduced from 87.2° to 77.8 °C, whereas that of EPO increased from 65.6 °C to 70.2 °C. Glass-FRP was tested in parallel, and exhibited no change to performance across the entire conditioning protocol.